2019
DOI: 10.26873/svr-775-2019
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE THREE DIMENSIONAL COMPUTED TOMOGRAPHY (CT) SCANS AND ANATOMICAL INVESTIGATION OF RABBIT (Oryctolagus cuniculus) AND CAT (Felis domestica) SKULL

Abstract: This study was conducted to elucidate the comparative anatomical features of the skull of rabbits and cats using CT scans. Adult healthy New Zealand rabbits and Domestic Baladi cats of both sexes, were prepared for X-ray and CT scan of the heads at different positions. The heads were also processed for bone preparation and were photographed at various views. Some measurements were taken to exhibit the main differences between the two animal species. There was a cranial pharyngeal canal in the basisphenoid bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The bony palate consisted of the palatine processes of the incisive bone (rostrally), the palatine processes of the maxillae (in the middle), and the horizontal part of the palatine bone (caudally). Similarly, Moselhy and Mahdy (2019) reported that the bony compartment of the hard palate is mostly formed by the palatine processes of the incisive bone, while the horizontal part of the palatine bone forms about eighth of it. The bony palate was characterized by presence of palatine fissure that appeared as an elongated heart‐shape with its base directed caudally.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The bony palate consisted of the palatine processes of the incisive bone (rostrally), the palatine processes of the maxillae (in the middle), and the horizontal part of the palatine bone (caudally). Similarly, Moselhy and Mahdy (2019) reported that the bony compartment of the hard palate is mostly formed by the palatine processes of the incisive bone, while the horizontal part of the palatine bone forms about eighth of it. The bony palate was characterized by presence of palatine fissure that appeared as an elongated heart‐shape with its base directed caudally.…”
Section: Discussionmentioning
confidence: 89%
“…Due to absence of canines, a large gap, the diastema, separated the incisors from premolar teeth. The diastema is a characteristic feature of herbivorous animals including lagomorphs (Brewer, 2006; Moselhy & Mahdy, 2019; Smith, 2013), rodents (Vaughan, Ryan, & Czaplewski, 2015), Artiodactylae, and Perissodactylae (Sachdev et al, 2020). It is longer in in grass eating animals than in leaf eating ones (Ardran, kemp, & Ride, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the skull indices obtained from these cranial measurements are quite effective in distinguishing or identifying morphological types (21). For this reason, various craniometric measurements have been used in the studies in determining the morphological variations between the domestic and wild cat species (6,8,14,30,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The medical imaging methods such as computed tomography is used commonly in displaying skull and the related complex anatomic structures especially in the pets such as cat, obtaining craniometric and volumetric measurement values from these images, and assessing the pathological conditions in the region (14,23). The present study is the first attempt to determine the morphometric and volumetric values of skull using CT and three -dimensional modelling in adult Van cats and reveal the biometric differences of these values between the males and the females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation